Educational Technologies for Strengthening Students’ Socio-Pedagogical Adaptation - Amonov , Mirjon (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article examines the pedagogical conditions for developing students’ adaptation to socio-pedagogical activities, the factors influencing its development, and the role of modern educational technologies. In addition, the scientific and pedagogical foundations for developing adaptive competence in the process of preparing future teachers for professional activity within the higher education system are analyzed.